Effects of zinc and allopurinol in ameliorating oxidative stress in lead-exposed workers - Dawser Khalil Ismaiel (University of Mosul, 2005)
Background: Oxidative stress has been recently implicated in the pathogenesis of acute and chronic exposure to lead. Consequently, the potential role of using antioxidants of various types to provide protective effects became a major task in this respect. Objective: This study was designed to explore the potential antioxidant effects of zinc and allopurinol in ameliorating the oxidation stress induced due to chronic exposure to lead. Methods: Twenty-four male workers, chronically exposed to lead, were enrolled in the study and treated with a single daily dose of 50 mg zinc sulfate and 100 mg allopurinol for 2 months. Erythrocyte and plasma MDA, GSH; blood lead, plasma copper and zinc level were measured each month during treatment and one month later after termination of treatment. Only eighteen workers completed the study. Results: During treatment, zinc and allopurinol significantly reduced excessive MDA production and elevated GSH level in association with decreasing blood lead level and improving the picture of the essential trace elements, copper and zinc in the plasma which were previously altered as a result of lead exposure. Conclusion: the use of antioxidants like zinc and allopurinol successfully eliminated the oxidative consequences of lead exposure, and the treatment should be continuously maintained as long as there is exposure to lead.